2016
DOI: 10.1017/s1352465816000357
|View full text |Cite
|
Sign up to set email alerts
|

Schema Therapy for Personality Disorders: a Qualitative Study of Patients’ and Therapists’ Perspectives

Abstract: Patients and therapists found some aspects of the schema therapy protocol helpful. Their views about which aspects are unhelpful and their recommendations need to be taken into consideration when adjusting the protocol and implementing schema therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…The treatments specified in the studies were delivered in an individual or group format, or a combination of both; these included DBT, MBT, art therapy, peer support group, and standard community mental health services [ 22 ]. However there has only been one qualitative paper on the experiences of participants receiving ST for treatment of a personality disorder [ 24 ]. In that study participants described helpful aspects of the treatment as the therapy relationship, specific schema techniques, and self-understanding facilitated by the schema model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatments specified in the studies were delivered in an individual or group format, or a combination of both; these included DBT, MBT, art therapy, peer support group, and standard community mental health services [ 22 ]. However there has only been one qualitative paper on the experiences of participants receiving ST for treatment of a personality disorder [ 24 ]. In that study participants described helpful aspects of the treatment as the therapy relationship, specific schema techniques, and self-understanding facilitated by the schema model.…”
Section: Introductionmentioning
confidence: 99%
“…Unhelpful aspects reported included perceived lack of preparation for strong negative emotions generated in the therapy and insufficient number of sessions. Whilst these patients all met criteria for a personality disorder, none of them had BPD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used their 75th percentile as a cut-point for the global Eating Disorder Examination Questionnaire (EDE-Q 6.0) (Fairburn and Beglin, 2008 ) score, indicating “probable eating disorder case.” However, we extended their criteria to additionally include participants who reached the 75th percentile on any of the 4 EDE-Q subscales. Specifically, to be included in the final data set, participants were required to meet at least one of the 2 inclusion criteria: (Young et al, 2003 ) a global EDE-Q score of 2.3 or higher, in conjunction with repeated bingeing episodes and/or use of exercise or other compensatory behavior over the past 4 weeks (Mond et al, 2004 , 2006 ); and/or (de Klerk et al, 2016 ) a mean score at or above the 75 percentile on at least one of the EDE-Q subscales—Restraint: 2.2; Eating Concern: 1; Weight Concern: 2.8; Shape Concern: 3.5.…”
Section: Methodsmentioning
confidence: 99%
“…Schema Therapy (ST) was developed to address long-standing psychological disorders and entrenched personality traits (Young et al, 2003 ), and a growing number of studies have demonstrated its effectiveness (Masley et al, 2012 ; Jacob and Arntz, 2013 ; de Klerk et al, 2016 ). ST is based on the notion that Early Maladaptive Schemas (EMS) develop as a result of the interaction between temperament and unmet core emotional needs during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on other patient populations, such as forensic patients, patients with cluster C PD and patients with cluster B PD, also confirmed the efficacy of ST on these patient populations (Bernstein et al 2007). Other studies are shifting their focus to how ST can be used to treat depression (Renner et al 2017), on what makes it such an efficient multidiagnosis therapeutic model (Lemmens et al 2016), and on exploring different perspectives of ST from the patient and the therapist's point of view (de Klerk et al 2017).…”
Section: Introductionmentioning
confidence: 99%